SOSIALISASI DAN PEMBENTUKAN PUSAT INFORMASI DAN KONSELING REMAJA (PIK-R) DI PONDOK PUTRI ASSALAM NAGA BERALIH - Yakub, Elni; Purnama, Aura Laddiya; Zain, Salsabila Tusyifah; Karima, Najla; Jannah, Miftahul; Ardhian, Teguh Muthi; Lutfi, Fitryyah; Desta, Indah (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Judging by the changing times, the thinking patterns and daily habits of teenagers have also changed so that judging from the environment and people around us, many teenagers have indications of emotional disorders or mental disorders which cause psychological changes that disrupt teenagers' daily lives. It can be seen that unrest is growing day by day and as an effort to prevent and eradicate it, it has been socialized and the Youth Information and Counseling Center (PIK-R) was formed. From the implementation of the formation of PIK-R, it is hoped that the new organization that the students create can become a forum for female students to increase their insight, skills and potential. And it is also hoped that the establishment of PIK-R can help female students with information about teenagers, probation, higher education, or other things. It is hoped that it can also be a place for peer counseling to alleviate and find solutions to the problems they are experiencing, which will later be supervised by teachers BK Pondok Putri Assalam Naga Beralih.